Avaliação do potencial tóxico do extrato hidroalcoólico de Pradosia huberi Ducke sobre o sistema reprodutor masculino e órgãos vitais de ratos e sua prole - Santos, Elane Cristina Silva dos (2012)
Since ancient times plants are used for medicinal purposes to treat, cure and prevention diseases. Pradosia huberi Ducke (Sapotaceae) is a medicinal plant commonly used by Amazonian communities for their antiulcerogenic and gastroprotective activities. Considering the popular use of this species, the presence of bioactive compounds with potential toxic effects on the male reproductive system, and the lack of scientific studies on the reproductive toxicity, this work aimed to investigate the toxic effects of P. huberi on fertility, offspring and vital, reproductive organs of rats. Wistar rats were divided into control and treated groups (n = 15). The control and treated groups received distilled water and hydroalcoholic extract of the stem bark of P. Huberi (PH-EHA), respectively, at doses of 1.22, 6.1 and 30.5 mg/kg body weight, orally and once daily, for 63 days, a period that correspond to the complete spermatogenic cycle of this species and the period of epididymal transit. The animals were killed on day 64. To investigate the toxic potential of PH-EHA on the reproductive system of rats the following parameters were evaluated: occurrence of clinical signs of general toxicity, daily consumption of water and food, biochemical and hematological tests, body weight, weight of vital organs, the reproductive organs and the accessory sex glands, sperm production, sexual behavior, genotoxicity and general development, and behavior of the offspring. The oral exposure to PH-EHA at doses of 1.22 and 6.1 mg/kg did not alter the body weight of rats, though the dose of 30.5 mg/kg caused a reduction in body weight of animals from the 35th day of treatment. This finding was corroborated by the decrease in food intake by these animals. The weight of kidneys, liver, lung, brain and pituitary, the testis, epididymis, seminal vesicles and prostate of the treated animals did not significantly change in relation to the weights of the control group. The administration of the extract did not cause significant changes in the hematologic and biochemical profile of rats. The production of gametes and their morphology did not differ between control and treated groups. Treatment with PH-EHA did not affect male sexual behavior, but caused an increase of 14.3% and 10.8% in the pre-implantation loss index, a reduction of 14.3% and 10.8% in implantation index, and a reduction of 5.6% and 8.2% in the post-implantation loss index of female rats mated with rats treated with 6.1 mg/kg and 30.5 mg/kg of PH-EHA, respectively. Morphological abnormalities were observed in stillborn offspring from dams mated with rats exposed to 30 mg/kg of PH-EHA. The general development, Reflexology and behavioral of the offspring were not affected by treatment. The results indicate a possible toxic action of EHA-PH in Wistar rats, with evidence of mutagenic and adverse effect on fetal development, as evidenced in the experimental model studied.